ANALISIS DAYA MINAT MAHASISWA BERWIRAUSAHA - Rihanna, Astuty; Wolor, Christian Wiradendi; Marsofiyati (Value : Journal of Management and Business, 2024)
The aim of this research is to find out in depth about students' perceptions regarding interest in entrepreneurship, the influencing factors, and the benefits of entrepreneurship for the students themselves. This topic is bassed on the data results of the low percentage of students' interest in entrepreneurship. The techniques used in collecting research data were observation and interviews with a case study approach. There were 4 informants interviewed to obtain data who focused on answering each research question. The results of the data obtained show that students understand the concept of interest in entrepreneurship, but it can be influenced by a number of factors and the benefits of entrepreneurship.